Fighting Termination of Investigation Using Universal Sweeping Methods PMH Lawsuit - Wahyono, Dwi (KnE Social Sciences, 2025)
Police officers must act professionally, carefully, and cautiously when stopping an investigation from a report from the public, by stating that they did not find a criminal act in the report, so as not to harm the law that is just. Legal efforts to fight the act of stopping the investigation when there are indications that it is not carried out professionally, carefully, and cautiously, even if it is felt that there is an interest of the investigator or the investigator’s superior or a certain party who has very strong economic or political power, is not regulated by Law Number 8 of 1981 concerning Criminal Procedure Law. This study aims to find a legal breakthrough to fight the termination of the investigation in a case that is indicated as a criminal act. This study was conducted with a legislative and conceptual approach. From analyzing the results of the discussion, it can be seen that a lawsuit for unlawful acts based on Article 1365 of the Civil Code can be used as a court order to ’force’ investigators to continue the investigation process to the investigation stage, so that justice, which is the crown of law enforcement, can be achieved.